State public enterprise and economic development - Kumar, Kamesh; Kashyap, Priti (New Delhi : Northern Book Centre, 1994)
Case study of Bihar, India.
Includes bibliographical references (p. [213]-219) and index.
Keywords: Government business enterprises -- India; India -- Economic policy -- 1991-